Methodological Considerations on Psychological Diagnosis and Consulting in Clinical Settings - Carmela, Mento; Flavia, Perrone; Vittorio, Lenzo; Catena, Silvestri Maria (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: The interest of diagnosis in clinical psychology is growing, but psychological diagnosis is a complex construct to describe because it is not a static process. It can be subject to change due to continuous evolutions/involutions present in a person’s psychic life. This review aims to describe the concept of psychological-clinical diagnosis. Method: We have carried out, following PRISMA guidelines, a systematic review of literature on Pubmed. Data for this systematic review have been collected in compliance with the reporting elements used for systematic reviews and metanalysis. Search terms were "Psychological diagnosis” AND “Psychological formulation”. Results: Psychological diagnosis can be defined as a process through which clinicians aim to know people's psychic functioning to investigate conscious and unconscious, healthy or pathological psychic dimensions. Psychological diagnosis has great importance in the clinical setting. Conclusion: Psychological diagnosis can be carried out at different levels, according to the context in which it is applied, using a multi-instrumental and multidimensional to investigate the state of an individual's functioning. The literature about this topic is poor and often connected to psychiatric diagnosis, which reduces its particular features. In light of this, it is important to give an overview of the concept of psychological-clinical diagnosis.